TRAFFICKING DI WILAYAH PERBATASAN - Widayatun Widayatun (LIPI Press, 2008)
The number of women migrating for work from Indonesia has steadily risen since the mid 1980’s; and by the year 2000 had increased to over 300,000 migrants. A significant number of Indonesian women voluntarily migrate to work are trafficked for sexual and labor exploitation in Malaysia and Singapore. This article explores trafficking problems and situation in Indonesia, especially focused in the border areas. International definitions of trafficking recognize a broader spectrum of abuses. In Indonesia, the most commonly recognized sectors into which women and children are trafficked in Indonesia include: migrant work, domestic work, sex work and servile marriage in the form of mail order brides. People from several areas of Java, Sumatera and Kalimantan who voluntarily migrating for work as domestic servants, later found themselves coerced into abusive conditions. Among them are Indonesian women who were recruited by false promises of employment and later coerced into prostitution or forced labor. Other cases show that ethnic Chinese women and teenage girls in the West Kalimantan district are recruited as mail-order bridges for men in Taiwan, Hong Kong, and Singapore. The Indonesian government has made significant efforts towards implementing a framework of action to address trafficking abuses against Indonesian women and children. Along with governmental actions, Indonesian civil society organizations (including NGOs and universities) have also increased their attention to the issue of trafficking in persons. Civil society organizations are now more effectively conducting research on trafficking related issues, implementing prevention and awareness raising activities in high risk communities, providing victim protection services such as legal aid case-handling and reintegration support, and advocating for increased law enforcement.